ANCAMAN DALAM TRANSAKSI ELEKTRO DI MASYARAKAT YANG DI ATUR DALAM UNDANG – UNDANG NOMOR 11 TAHUN 2008 TENTANG ITE BERUBAH MENJADI UNDANG - UNDANG ITE NOMOR 19 TAHUN 2016 - Rachell Abigael, Ellena; Rahayu, Diana Fitria; Ul Hosnah, Asmak (Jurnal De Jure Muhammadiyah Cirebon, 2023)
This journal provides an explanation of fraud that occurs online. People who are smart in developing creativity using technology. In this activity the community also participates in helping the country in improving the country’s economy. In this journal the author wants to inform you about the advantages and disadvantages of online transactions, not only the advantages but also the disadvantages that can be experienced by producers or consumers online. Many online transactions are carried out on social media, which in the current electronic age makes shopping or doing things on the internet very easy and more practical to do. Fraud is rampant on social media, where buyers are often cheated by online traders, even though carrying out online transactions is positively easier, cheaper and more affordable, there is a lot of fraud that occurs in society and fraudsters sometimes cannot be found because of the large number traders who use fake identities, so that buyers can trust them. The government is trying to prevent and provide sanctions against perpetrators of fraud which cause a lot of harm to society. Apart from that, the journal created aims to find out whether the government has ideally cleaned up the fraudsters who are rampant in this internet age, and what efforts have been made by the government in providing sanctions to the perpetrators and why there can be changes to Law No. 11 of 2008 concerning ITE became ITE Law Number 19 of 2016. Keywords: ITE Law Number 19 of 2016, Online Buying and Selling Sites, criminal acts of fraud.